Implementasi Nilai-Nilai Keagamaan pada Masyarakat Gampong Meunasah Baet Kecamatan Krueng Barona Jaya - samsurizal, nazifa; Ghazalba, Ahmad; Shintya, Melfa; Humaira, Anggi; Chairana, Raji; Shiddikia, Nanda; Wiranda, Oja; Rahmatillah, Rais; Azkia, Ulfa; Syifa, Maulidhia; Maulana, Nouval; Firdaus, Muhammad; Mauleni, Silvia; Alvin, Teuku; Nazmi, Syahrul; Putri, Nabila; Izzaturrahman, Fauzan (Jurnal Riset dan Pengabdian Masyarakat, 2025)
Community Service Lectures can bring about new changes in society, one of which is religious and social education, so that there will be an impact from the presence of community service lecture participants. Like the community service lectures held in the village of Gampong Meunasah Baet, Aceh Besar Regency, students as agents of change can make a real impact and contribution to society through this KPM program. In this case, the aim is to determine the impact of community service lectures on religious activities for children and parents in Gampong Meunasah Baet. This community service lecture activity is not just a form of community service but is also useful for students for social interaction, developing personal potential, forming personality or attitudes, and applying knowledge in the field. In this way, this community service course provides a real learning experience that cannot be found on campus. This type of research is field research with a qualitative descriptive approach whose object is Gampong Meunasah Baet and the subjects are children and parents